Nursing care for children with leukemia in a high complexity hospital (Research, Society and Development, 2021)
Introduction: Childhood cancer is considered a rare disease, being progressive and of great relevance to public health in the country. When associated with tumors, leukemia is considered to be the second leading cause of mortality mainly in the age group of five to nine years. The role of the nurse has a primary role in the recovery and maintenance of the child's healthy life conditions. Objective: To know the care provided by nursing to children with leukemia in the hospital environment. Methodology: This is a qualitative research with a descriptive approach. It was performed at the pediatric oncology clinic of a philanthropic hospital in Teresina-PI. The research subjects were all nurses and seven nursing technicians. Data were collected from September to November 2017, using a semi-structured interview script. Result: Three nurses and seven nursing technicians participated in the study and, from the reports, two thematic categories emerged: Nursing care for children with leukemia during hospitalization; Nursing incentive for children with leukemia to remain hospitalized until recovery. It is evident the use of strategies to provide well-being of the child / family binomial through welcoming together with humanized assistance; guidance on the procedures they will have to undergo in the hospital environment; support for family members and promotion of children's leisure, time to play. Conclusion: This study contributed to the expansion of nursing knowledge about the care provided to children with leukemia, as well as in the discussion and implementation of actions that can promote the improvement of the quality of life of these children.